Pendampingan Pemilihan Portofolio Keuangan Syariah bagi Ibu PKK Kelurahan Kadungora Kecamatan Kadungora: Guidance in Selecting Sharia Financial Portfolio for PKK Women in Kadungora Village, Kadungora District - Yayat Rahmat Hidayat; Nanik Eprianti; Popon Srisusilawati; Mohamad Andri Ibrahim (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
The problem is that people still save in savings-and-loan cooperatives through arisan, which often ends in fraud. This is due to a lack of public knowledge and understanding of the types of Sharia financial products, and a lack of awareness of how to check financial portfolios that hold OJK permits, which contributes to the lack of public interest in using Sharia financial products. The community still has limited information about Sharia financial products. Therefore, to increase understanding and increase the use of sharia financial portfolios for the community in Kadungora village, it is necessary to assist the selection of sharia financial portfolios for PKK mothers who represent the Kadungora community. The purpose of this study is to provide the community, through PKK mothers, with knowledge about Sharia financial portfolio literacy and the benefits of Sharia financial portfolios in Kadungora Village. Mentoring activities using an innovative literacy approach are among the factors that support the Partner's goal, namely, increasing knowledge in Kadungora Village and increasing community interest in using sharia financial portfolios, thereby positively impacting the development of the sharia economy. The method in mentoring PKK mothers is by contacting and establishing cooperation with the village head in Kadungora village, then conducting an approach with a survey to Kadungora village, then gathering PKK mothers and providing an overview of mentoring activities, as well as providing literacy mentoring to PKK mothers about various types of sharia financial portfolios and the benefits, and how to calculate the profit of a sharia financial portfolio.